OPERATION PROCESS AND EXPERIMENTAL RESULTS OF CONTINUOUSLY FRUIT AND VEGETABLE DRYING EQUIPMENT - MANSUROV, OMON; XAMDAMOV, ANVAR; QODIROV, OLIMJON (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
The article describes the device of continuous drying of fruits and vegetables and the process of its operation. The drying devices currently used in industry and the processes and disadvantages of their operation are presented.The drying device is now compared to existing devices and the advantages are explained.